2009
DOI: 10.1080/10408340903001144
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Traffic-Derived Platinum Group Metals

Abstract: Subsequently introduced standards on exhaust gas emissions determine the development of motorization industry as well as stimulate the search for new environmentally friendly solutions for road transport. One of such pro-environmental solutions, directed toward reducing emissions of toxic exhaust components, has been a project concerning application of catalytic exhaust gas converters in mechanical vehicles which contained platinum group metals (PGM). Despite undeniable benefits, application of PGM in gas conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 135 publications
(114 reference statements)
1
5
0
Order By: Relevance
“…All concentrations were above the method quantification limit. Found concentrations for platinum ranged from 205 to 1445 ng g −1 , which is in the same order of magnitude as reported in the literature [ 29 32 ]. Concentrations of palladium ranged from 201 to 1230 ng g −1 , which is also in agreement with reported data [ 31 , 32 ].…”
Section: Resultssupporting
confidence: 80%
“…All concentrations were above the method quantification limit. Found concentrations for platinum ranged from 205 to 1445 ng g −1 , which is in the same order of magnitude as reported in the literature [ 29 32 ]. Concentrations of palladium ranged from 201 to 1230 ng g −1 , which is also in agreement with reported data [ 31 , 32 ].…”
Section: Resultssupporting
confidence: 80%
“…However, Pd and Pt can be converted into soluble forms, which become bioavailable and pose a serious threat to animals and plants [ 33 , 52 ]. Soil is one of the components of the environment most susceptible to PGE contamination [ 53 , 54 ]. Several studies have shown that human activity has caused an increase in the concentration of PGEs in the soil, especially near roads [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous studies on the uptake of PGMs into plants, animals, and the food chain [212,217]. While the release of metallic PGMs into the environment may not be considered particularly harmful because of their low toxicity, there are routes to bioavailability through platino-chloro complexes and amino-platino-nitrates [218]. Airborne auto catalysts particulates [213] deposited in rats lungs, rather than being inert, were apparently dissolved to some extent because they were present in blood and other organs [219], indicating that ingestion via the lungs was possible.…”
Section: Dissipationmentioning
confidence: 99%